Anti-IgE monoclonal antibodies as potential treatment in COVID-19. (4th May 2021) - Farmani, Ahmad Reza; Mahdavinezhad, Forough; Moslemi, Rohollah; Mehrabi, Zeinab; Noori, Alireza; Kouhestani, Mahsa; Noroozi, Zahra; Ai, Jafar; Rezaei, Nima
Abstract: Coronavirus disease 2019 (COVID-19) is associated with irreversible effects on vital organs, especially the respiratory and cardiac systems. While the immune system plays a key role in the survival of patients to viral infections, in COVID-19, there is a hyperinflammatory immune response evoked by all the immune cells, such as neutrophils, monocytes, and includes release of various cytokines, resulting in an exaggerated immune response, named cytokine storm. This severe, dysregulated immune response causes multi-organ damage, which eventually leads to high mortality. One of the most important components of hypersensitivity is immunoglobulin E (IgE), which plays a major role in susceptibility to respiratory infections and can lead to the activation of mast cells. There is also a negative association between IgE and IFN-α, which can reduce Toll-like receptor (TLR) nine receptor expression and TLR-7 signaling to disrupt IFN production. Moreover, anti-IgE drugs such as omalizumab reduces the severity and duration of COVID-19. In addition to its anti-IgE effect, omalizumab inhibits inflammatory cells such as neutrophils. Hence, blockade of IgE may have clinical utility as an immunotherapy for COVID-19.